Auditory Morphological Knowledge Among Children With Developmental Dyslexia. (3rd March 2016) - Schiff, Rachel; Cohen, Miki; Ben-Artzi, Elisheva; Sasson, Ayelet; Ravid, Dorit
ABSTRACT: The aim of the present study is to examine the morphological knowledge of readers with developmental dyslexia compared to chronological age and reading-level matched controls. The study also analyzes the errors dyslexics make and their metamorphological awareness compared to controls. Participants included 31 seventh-grade dyslexic children and two matched control groups of normal readers: 34 seventh graders matched for chronological age and 32 third graders matched for reading age. Two tasks were administered via the auditory modality—morphological priming and morphological analogies task. We also performed error analysis and a metamorphological interview. Our analyses reveal that although dyslexics perform equally to chronological age matched controls on the priming task and similarly to reading-level matched controls on the morphological analogies task, their errors and metamorphological awareness are qualitatively different.